The rule of law and investment in intangible capital: Evidence for the EU-16, 1996-2017 - Felix Roth (University of Hamburg, Chair of International Economics, 2022)
This paper analyses the relationship between the rule of law (RoL) and intangible capital investment by businesses within a sample of 16 European countries, over the period from 1996 to 2017. Studies on the effects of RoL on intangible capital investment are scarce, hence, the relevance of empirical research in this area. When controlling for endogeneity, the study found a coefficient of 2.0 for the relationship between RoL and investment in intangibles, confirming the significant and positive relationship between the two and highlighting RoL as a driving factor of investment in intangibles and, hence, labour productivity growth in the EU-16.
Keywords: E02; E22; O34; O43; O52; P14; 330; rule of law (RoL); intangible capital investment; labour productivity growth; European Union (EU)